2007
DOI: 10.1074/jbc.m704886200
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-derived Peptidoglycans Constitute Pathogen-associated Molecular Patterns Triggering Innate Immunity in Arabidopsis

Abstract: The innate immune system is a host defense mechanism that is evolutionarily conserved from insects to human and is mainly involved in the recognition and control of the early stage of infection in all animals (1). Over the last decade, it has become increasingly evident that also plants have acquired the ability to recognize "non self" via sensitive perception systems for components of microorganisms called pathogen-associated molecular patterns (PAMPs) 2 (2-4). As classically defined, PAMPs are highly charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
224
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(237 citation statements)
references
References 79 publications
9
224
0
1
Order By: Relevance
“…15 PGN is an essential structural component of the bacterial cell wall and acts as a PAMP on Arabidopsis. 16,17 It is therefore plausible that PGN constitutes a ligand for any of the three LysM motifs of CERK1. To test this hypothesis, we purified Pto DC3000 PGN as described by Erbs et al 16 Both chitin and PGN induced ROS generation on Col-0 plants as expected (Fig.…”
Section: Cerk1 a Lysm Receptor Kinase Required For Fungal And Bactermentioning
confidence: 99%
“…15 PGN is an essential structural component of the bacterial cell wall and acts as a PAMP on Arabidopsis. 16,17 It is therefore plausible that PGN constitutes a ligand for any of the three LysM motifs of CERK1. To test this hypothesis, we purified Pto DC3000 PGN as described by Erbs et al 16 Both chitin and PGN induced ROS generation on Col-0 plants as expected (Fig.…”
Section: Cerk1 a Lysm Receptor Kinase Required For Fungal And Bactermentioning
confidence: 99%
“…MPK3 in the response to a diversity of stresses, e.g., treatment with the plant pathogen Pseudomonas syringae, various pathogen-associated molecular patterns, wounding, and oxidative stress (18,(25)(26)(27). The 1,000-bp promoter region of Trxh8 harbors six VRE copies (Fig.…”
Section: Investigation Of Vre Regulation In Two Potential Vip1 Targetmentioning
confidence: 99%
“…Polymeric PGNs from Gram-positive and Gram-negative bacteria or a mixture of oligomeric muropeptides derived thereof act as PAMPs in the model plant Arabidopsis thaliana (18,19). Our previous experiments suggested that the carbohydrate backbone of PGN is important for its immunogenic activity and that PGN is recognized in a receptor-mediated manner in Arabidopsis (19).…”
mentioning
confidence: 99%
“…Our previous experiments suggested that the carbohydrate backbone of PGN is important for its immunogenic activity and that PGN is recognized in a receptor-mediated manner in Arabidopsis (19). Plant lysin-motif (LysM) domain proteins have been widely implicated in the recognition of GlcNAc-containing glycans.…”
mentioning
confidence: 99%